Electrochemical propertiesand thermal stability of cup-like shape gold nanostructures - Kynclová, H. (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2015)
Nanostructured surfaces are useful in enlargement of electroactive area of sensing electrodes. The electrodes are very sensitive with maintaining small electrode geometry. In this study, surfaces modified by cup-like gold nanoparticles were fabricated by electrochemical methods. Subsequently, electrochemical properties and thermal stability of fabricated nanostructured electrodes were studied. Thereafter, the electrochemical results were compared with unmodified flat gold layer and contribution of nanostructuring was evaluated. Stability of nanoparticles after thermal vacuum and air pressure treatment was studied using scanning electron microscope. These results are useful for subsequent research of nanostructured sensors.
Keywords: gold nanoparticles; nanostructured electrode; electrochemical impedance spectroscopy; cyclic voltammetry